Tokyo ghoul : re. 10 - Ishida, Sui (VIZ Media LLC, 2019)
"Haise Sasaki is no more. In his place, Ken Kaneki has emerged and accepted the role of the One-Eyed King. He sees a vision of the future where Ghouls and humans can coexist. But a faction at the CCG wants to prevent that peace by any means necessary, and the inevitable death toll means nothing to them" --